‟LE RITE” (1969) D’INGMAR BERGMAN: L’ACTEUR-COMME-ACTEUR ENTRE L’‟ANAGNORISIS” ET LA FRAGILITÉ DE L’IDENTIFICATION - CÂMPEAN, Alexandra Noemina (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
Ingmar Bergman’s The Rite (1969): the Actor-as-Actor between Anagnorisis and Fragility of Identification. The present paper analyses the strange identification experienced by the Bergmanian actor-as-actor, due to a perpetual memory of the body. We will examine the manner in which the actor who plays the role of the actor passes through a painful and disarticulated identification, originated in August Strindberg’s radiations of the ego (Ausstrahlungen des Ichs). Accordingly, the radiations are not only writings in the first person, but also egotistical discourse; binding the ego on the stage, the playwright’s world becomes not only a psychic experience, but also a diurnal dream lived with the eyes wide open (as in the plays The Road to Damascus and A Dream Play). Therefore, in the film The Rite (Riten, 1969, TV movie), the total and stylized actor enacts the virtue of the crime in order to re-cognize himself; in this context, the achievement of his persona confirms the thorough execution of a murder – that is to say that the actor’s visage foreshadows the melancholic soleil noir of the Universal tragedy.